2005
DOI: 10.1002/jcu.20168
|View full text |Cite
|
Sign up to set email alerts
|

Patients' tolerance and early complications of transrectal sonographically guided prostate biopsy: Prospective study of 300 patients

Abstract: TRS-guided prostate biopsy can be performed without local anesthesia in 90% of patients. Prophylactic antibiotics are mandatory to minimize approximately infectious complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…However, vasovagal reactions during TRUS-guided prostate biopsy without the use of local anesthetic has been reported in 1 out of 300 men. 20 In our study, symptoms associated with systemic lidocaine toxicity occurred in 2% of patients. There is an abundance of vessels in the area targeted for local anesthetic infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…However, vasovagal reactions during TRUS-guided prostate biopsy without the use of local anesthetic has been reported in 1 out of 300 men. 20 In our study, symptoms associated with systemic lidocaine toxicity occurred in 2% of patients. There is an abundance of vessels in the area targeted for local anesthetic infiltration.…”
Section: Discussionmentioning
confidence: 95%
“…It is relatively uncomplicated, can be carried out in most cases as an outpatient procedure and Sheikh et al reported that the frequency of pain in their patient cohort was 57.3%, although in most cases it was described as being mild to tolerable; only 3.3% of the patients reported a pain so intense that the procedure had to be aborted [7]. Other researchers have reported intense to intolerable pain at frequencies varying from 22 to 30% [8][9][10].…”
Section: Discussionmentioning
confidence: 95%
“…A precise comparison of the rate of infection in the literature is difficult since the definitions of an infection differ among studies. Fever is quoted as occurring at an incidence of 1.5 [12] and 1.7% [7,8], respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sheikh and colleagues recommend transperineal removal of tissue rather than a transrectal biopsy in patients with severe hemorrhoids. 5 Any abnormality that may increase the risk of bleeding should be routinely evaluated by history-taking and brief proctological examination before starting the procedure. In our case, the patient had no history of perianal pathology or bleeding diathesis.…”
Section: Discussionmentioning
confidence: 99%